Advancing Cardiorespiratory Physiotherapy Practice in a Developing Country: Surveying and Benchmarking. (15th December 2019) - Okasheh, Rasha; Al-Yahya, Emad; Al-Khlaifat, Lara; Almasri, Nihad; Muhaidat, Jennifer; Qutishat, Dania
Abstract : Management of noncommunicable diseases requires the adoption of multidisciplinary interventions that targets the modification of risk factors. Cardiovascular and respiratory diseases are amongst the four main killers of noncommunicable diseases. Physiotherapists specializing in cardiorespiratory physiotherapy are in a critical position in the management of health behaviors associated with noncommunicable diseases. However, the current context of health service in Jordan does not provide sufficient support and recognition for the delivery of specialized physiotherapy services. Objectives. The primary aim of this study was to describe cardiorespiratory physiotherapy service in Jordan. The secondary aims of this study were to: (i) Identify benchmarks from international contexts and guidelines for the delivery of cardiorespiratory physiotherapy service. (ii) Identify gaps and areas for development in the current delivery of cardiorespiratory physiotherapy service. Methods. This two phase study included a survey and a conceptual review with benchmarking. Following ethics approval, a cross sectional survey of physiotherapists practicing in Jordan was conducted. In phase 1, a survey was developed to describe the relevant dimensions of cardiorespiratory physiotherapy service. In phase 2 a conceptual review of the literature was performed to identify domains of service delivery and criteria required for optimal delivery of cardiorespiratory physiotherapy service. In the discussion we integrated the results of the survey within the benchmarks that emerged from the conceptual review of literature in order to identify gaps and areas for development in the current delivery of cardiorespiratory physiotherapy service. Results. Phase 1: Data emerging from the survey suggests that Physiotherapists in Jordan lack training and autonomy, preventing them from acquiring advanced roles particularly cardiorespiratory physiotherapy that requires specialised knowledge and skills. The current delivery of the service is limited to acute interventions, and is based on limited, unstructured referral from physicians depriving the patients from the service. The context of health service in Jordan does not provide sufficient recognition for physiotherapy; neither does it support the delivery of multidisciplinary interventions by appropriate regulations and policies. Phase 2: The following three domains emerged from the literature and were used for describing cardiorespiratory physiotherapy in Jordan: people, scope of practice, and context of practice. Conclusion. Advancing practice requires developing competencies relevant to cardiorespiratory physiotherapy particularly diagnosis, health promotion, and prevention. It is recommended that health authorities should develop regulations and policies that promote the recognition and integration of physiotherapists in the healthcare system, as well as facilitating the implementation of patient centred, multidisciplinary interventions.